Total synthesis of (+/-)-nardoaristolone B and its analogues - Handore, Kishor L.; Reddy, D. Srinivasa (Organic Letters, 2014)
The first total synthesis of nardoaristolone B, a nor-sesquiterpenoid with an unusual fused ring system and having protective effects on the injury of neonatal rat cardiomyocytes, has been accomplished. Stereoselective synthesis of its novel analogues inlcuding exo-cyclopropyl ring fusion is also part of this disclosure. In addition, an alternate and more efficient one-step method to make a 3/5/6 tricyclic ring system using the Robinson annulation method has been developed toward the generation of a library of compounds around this skeleton.

Total syntheses and biological evaluation of (+/-)-botryosphaeridione, (+/-)-pleodendione, 4-epi-periconianone B, and analogues - Handore, Kishor L.; Jadhav, Prakash D.; Hazra, Bibhabasu; Basu, Anirban; Reddy, D. Srinivasa (ACS Medicinal Chemistry Letters, 2015)
The total syntheses of (+/-)-botryosphaeridione, (+/-)-pleodendione, (+/-)-hoaensieremodione, 4-epi-periconianone B, and their analogues have been accomplished for the first time. All the synthesized target compounds were screened in neural anti-inflammatory assays using LPS induced microglia cells (N9). Among them, compounds 1 and 21 were identified as potential lead compounds for further profiling.
Keywords: antineuroinflammatoty agents; bohyosphaeridione; Natural product; pleodendione; Total synthesis

Total synthesis of (-)-nardoaristolone B - Ople, Rohini S.; Handore, Kishor L.; Kamat, Nidhi S.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2016)
A stereoselective total synthesis of (-)-Nardoaristolone B, a nor-aristolane sesquiterpenoid natural product with an unusual 3/5/6 tricyclic ring system is described. The highlights of the present work includes use of (+)-(R)-Pulegone as a chiral-pool starting material, ring-closing metathesis, allylic oxidation and stereoselective cyclopropanation. In addition, a new analogue of Nardoaristolone B (minor product from the final step) was isolated in pure form and fully characterized with the help of single-crystal X-ray analysis.
Keywords: Chiral pool; cyclopropanation; Nardoaristolone B; Natural products; Total synthesis

Total synthesis and biological evaluation of cell adhesion inhibitors peribysin A and B: structural revision of peribysin B - Kalmode, Hanuman P.; Handore, Kishor L.; Rajput, Raveena; Shaikh, Samir R.; Gonnade, Rajesh G.; Kulkarni, Kiran A.; Reddy, D. Srinivasa (Organic letters, 2018)
Total synthesis of potent cell-adhesion inhibitors peribysins A and B has been accomplished for the first time in racemic form. A Diels-Alder/aldol sequence to build the skeleton and decoration of the desired functionalities of the targeted natural products using highly stereoselective operations are the highlights. The structures of synthesized peribysins were fully characterized using spectral data and single-crystal X-ray analysis. Through this total synthesis, the initially proposed structure of peribysin B has been revised. Furthermore, the cell-adhesion inhibition potential of the scaffold (two peribysins + three analogues) was confirmed using anti-adhesion assay.